Lectotypification of the name Regnellidium diphyllum (Marsileaceae) - Arana, Marcelo Daniel (Phytotaxa, 2015)
Regnellidium Lindman (1904: 2) is a genus that includes only the extant species Regnellidium diphyllum Lindman (1904: 14) in the family Marsileaceae Mirbel (1802: 126), which encompasses a total of three extant genera of aquatic, heterosporous ferns. While the other two genera within the family, Marsilea L. (1753: 1099) with 50–75 spp., and Pilularia L. (1753: 1100) with 3–6 spp., are nearly cosmopolitan in distribution, the extant species of Regnellidium is restricted to a small region of South America, found only in northeastern Argentina, southern Brazil, and Uruguay (Schultz, 1949; de la Sota & Mitchel 1970; Tryon & Tryon 1982; Kramer, 1990; Alonso Paz & Bassagoda, 2002; Cúneo et al., 2013). It was only in 1892, on the first Regnell expedition, that Lindman discovered the plants, which he described as Regnellidium (Lindman, 1904), on the banks of the Rio Grande do Sul, in southern Brazil. The species was not found again until November 1935, when it was located at Santa Maria by Dr. W. Rau and at São Leopoldo by Dr. J. Dutra (Johnson & Chrysler, 1938). Today it is widely cultivated in Botanic Gardens.